Perioperative Goal-Directed Therapy Using Invasive Uncalibrated Pulse Contour Analysis - Saugel, Bernd; Reuter, Daniel A. (Frontiers in Medicine, 2018)
"Perioperative goal-directed therapy" (PGDT) aims at an optimization of basic and advanced global hemodynamic variables to maintain adequate oxygen delivery to the end-organs. PGDT protocols help to titrate fluids, vasopressors, or inotropes to hemodynamic target values. There is considerable evidence that PGDT can improve patient outcome in high-risk patients if both fluids and inotropes are administered to target hemodynamic variables reflecting blood flow. Despite this evidence, PGDT strategies aiming at an optimization of blood flow seem to be not well implemented in routine clinical care. The analysis of the arterial blood pressure waveform using invasive uncalibrated pulse contour analysis can be used to assess hemodynamic variables used in PGDT protocols. Pulse contour analysis allows the assessment of stroke volume (SV)/cardiac output (CO) and pulse pressure variation (PPV)/stroke volume variation (SVV) and thus helps to titrate fluids and vasoactive agents based on principles of "functional hemodynamic monitoring". Pulse contour analysis-based PGDT treatment algorithms can be classified according to the hemodynamic variables they use as targets: PPV/SVV, SV/CO, or a combination of these variables. From a physiologic point of view, algorithms using both dynamic cardiac preload and blood flow variables as hemodynamic targets might be most effective in improving patient outcome. Future research should focus on the improvement of hemodynamic treatment algorithms and on the identification of patient subgroups in which PGDT based on uncalibrated pulse contour analysis can improve patient outcome.